Characterization and preparation of sago starch (SS) based reinforced with silver nanoparticle (SNP) - Ahmad, Zuraida; A.K. , Ahmad Ulwi; T., Maisarah; A., Maisarah (Trans Tech Publications Ltd., Switzerland, 2015)

(untitled)
This paper reported on the properties of sago starch (SS) films impregnated with different concentration of sliver nano-particles (SNP) of 100, 2000, 5000 rpm with weight ratio of 1% and 10% to be used as wound healing material. The SS films were prepared through film moulding technique by mixing aqueous SNP with SS, glycerol and water at weight percentage of 6.5:3.5:90. The performance of SS-SNP films produced is studied. The morphology study shows the existence of SNP embedded in the SS particles. SNP with 2000ppm has the biggest particle width but small in particle sizes, which make the SS-SNP film of 2000ppm is superior in thickness, denser and has lower moisture content compared to other SS-SNP film with different composition. The highest water absorption occurred in the SS-SNP of 100ppm, due to the high existence of pores in the network of amylose content in starch. SNP act as particulate reinforcement in the SS film meaning higher number of ppm made the film more brittle and easy to rupture. Thus, the SS-SNP film of 5000ppm has the lowest tensile strength and modulus for tensile strength and modulus. It can be concluded that the SS-SNP film of 2000ppm is suitable to be used as wound healing material, as the addition of 2000ppm SNP inside the SS films help in improving the properties of SS-SNP film produced.